Dança e infância: análise da percepção da dança com crianças no Sistema Integrado de Educação e Cidadania (SIEC) - COSTA, Nágela Shirlene Campos da (2019)
The purpose of this study is to analyze the process of perception of dance for children in the Integrated System of Education and Citizenship (SIEC). The aim of this study was to show how this process of perception, its significant aspects in the children 's life, is perceived. The theoretical-methodological framework focused on a qualitative research focusing on action research, analyzing the child's learning process from an understanding of how dance can contribute to the growth of critical awareness of these children and how they understand the dance and its importance in their lives. The research instruments used are based on playfulness through games, toys and games contained in the activities of rhythmic experiences, with the use of materials (chords, hula hoops, elastics, drawings, stories) of sung toys. The study partners are 10 (ten) children, at the age of 6, enrolled in the Integrated Education and Citizenship System (SIEC). The locus of the investigation is the SIF SIF, located in the Batista Campos neighborhood in Belém/PA. The findings of the study showed that through dance, children can increase their fields of knowledge, their expressiveness and their body perception, as well as enable them to have a more critical view of the social reality that is inserted.